1965
DOI: 10.1139/v65-249
|View full text |Cite
|
Sign up to set email alerts
|

The Photolysis of Carbon Disulfide and Carbon Disulfide – Oxygen Mixtures

Abstract: These data show that I from the second method has two NMe proton peaks in a ratio of 1:2 a t 6 = 4.28 and 4.90 upfield from benzene. All the other spectra contain these two peaks in the same ratio, but other peaks are also present. In the spectra of crude products and in the 90 and 100 OC sublimate from both methods, another pair of peaks is located a t approxiinately 6 = 4.25 and 4.78 upfield from benzene and in the ratio of 1:2. These two closely spaced pairs suggest the presence of two forms of Be(NNIe2)2 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

1966
1966
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(19 citation statements)
references
References 2 publications
(3 reference statements)
1
16
0
1
Order By: Relevance
“…Theoretical precision of the concentration measurements was much higher (in the FTIR experiments) than the reproducibility of the quantran yields, especially those at high PCS2. Although the quantum yields at PCS2 > 3 tort cannot be considered primary quantum yields for photopolymerization, they provide a link to the previous studies [de Sorgo et al, 1965;tVood and Heicklen, 1971b]. It is also possible that the size of the growing (CS2)x cluster affects its reaction efficiency with CS2".…”
Section: Because Of Complicating Lactors Involving Secondary Photolysmentioning
confidence: 99%
“…Theoretical precision of the concentration measurements was much higher (in the FTIR experiments) than the reproducibility of the quantran yields, especially those at high PCS2. Although the quantum yields at PCS2 > 3 tort cannot be considered primary quantum yields for photopolymerization, they provide a link to the previous studies [de Sorgo et al, 1965;tVood and Heicklen, 1971b]. It is also possible that the size of the growing (CS2)x cluster affects its reaction efficiency with CS2".…”
Section: Because Of Complicating Lactors Involving Secondary Photolysmentioning
confidence: 99%
“…There have been several reports of CS 2 photochemistry that have tried to illustrate the formation mechanism of S 2 fragments. In one study, de Sorgo et al observed transient absorption spectra of S 2 ( v = 0), but no S atoms were observed by that method. They concluded that S 2 must be formed by the reaction CS 2 * + CS 2 → 2CS + S 2 .…”
mentioning
confidence: 99%
“…In previous studies, high pressure polymerization (Whalley, 1960;Chan and Jonscher, 1969), photolysis (de Sorgo et al, 1965), chemical polymerization (Tsukamoto and Takahashi, 1986), laser-induced polymerization (Ernst and Hoffman, 1979;Matsuzaki et al, 1992;Desai et al, 1995), and plasma polymerization (Hirotsu, 1981;Asano, 1983;Sadhir and Schoch, 1996;Denisov et al, 1997) of CS 2 usually led to the formation of dark brown to black depositions or polymers. The structures of the polymers have been described as linearor crosslinked (CS 2 ) n for the 45 kilobar products or thermal decomposition of photopolymerization products (Whalley, 1960;Chan and Jonscher, 1969;Colman et al, 1996), as (CS) n for plasmalysis (Denisov et al, 1997), laser-induced aerosol (Ernst and Hoffman, 1979;Desai et al, 1995) or combustion (Cullis, 1972), and as [CS(S) m ] n (m ϭ 0, 1, 2 .…”
Section: Introductionmentioning
confidence: 94%